Analysis Determination of the Best Employee Using the Simple Additive Weighting Method - Haryo Kusumo; Achmad Solechan; Febryantahanuji Febryantahanuji (Advance Sustainable Science Engineering and Technology, 2023)
In a company, quality human resources are very important to carry out business processes in accordance with the vision and mission that has been set. CV. Jaya Abadi is a company engaged in the procurement and repair services of various electronic devices and was founded in 2015. To encourage the creation of ever-increasing performance productivity, CV. Jaya Abadi selects the best employees using a decision support system. One of the methods used is the Simple Additive Weighting (SAW) method. In this study, the data used consisted of internal data and external data. There are several criteria that are taken into consideration in selecting the best employees, namely discipline, quality of work, cooperation, and behavior. The SAW method is proven to be effective and practical in calculating to determine the best employee recommendations at CV. Jaya Abadi. Thus, decision makers can consider these recommendations according to the priorities set.